2008
DOI: 10.1196/annals.1410.065
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Levels in Brazilian Citizens of Distinct Socioeconomic and Cultural Levels

Abstract: We have analyzed the perceived stress index, the basal salivary cortisol levels, and the awakening cortisol response (ACR) in 86 volunteers of low (LSES) and high socioeconomic status (HSES). The LSES presented higher perceived stress index and basal salivary cortisol levels, nonaltered ACR, or cortisol diurnal rhythm. We have concluded that the LSES is associated with high perceived stress index and salivary cortisol levels, which could impact negatively in health, and that it is related to the daily life str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
(17 reference statements)
1
19
1
2
Order By: Relevance
“…For example, some studies found no association between SES and cortisol levels at wake-up (Kunz-Ebrecht et al, 2004; Ranjit et al, 2005a; Wright and Steptoe, 2005; Cohen et al, 2006a; Cohen et al, 2006b; Eller et al, 2006), while others found higher wake-up cortisol levels among higher SES groups (Brandtstädter et al, 1991; Steptoe et al, 2003; Bennett et al, 2004). The picture for CAR is even less consistent: some studies find no association (Steptoe et al, 2003; Steptoe et al, 2005; Cohen et al, 2006b; Eller et al, 2006; Garcia et al, 2008), others find a steeper CAR among high SES groups (Bennett et al, 2004; Ranjit et al, 2005a) and still others a flatter CAR among high SES groups (Kunz-Ebrecht et al, 2004; Steptoe et al, 2005; Wright and Steptoe, 2005). As for the diurnal slope, a few studies found no association between cortisol and SES (Steptoe et al, 2005; Cohen et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies found no association between SES and cortisol levels at wake-up (Kunz-Ebrecht et al, 2004; Ranjit et al, 2005a; Wright and Steptoe, 2005; Cohen et al, 2006a; Cohen et al, 2006b; Eller et al, 2006), while others found higher wake-up cortisol levels among higher SES groups (Brandtstädter et al, 1991; Steptoe et al, 2003; Bennett et al, 2004). The picture for CAR is even less consistent: some studies find no association (Steptoe et al, 2003; Steptoe et al, 2005; Cohen et al, 2006b; Eller et al, 2006; Garcia et al, 2008), others find a steeper CAR among high SES groups (Bennett et al, 2004; Ranjit et al, 2005a) and still others a flatter CAR among high SES groups (Kunz-Ebrecht et al, 2004; Steptoe et al, 2005; Wright and Steptoe, 2005). As for the diurnal slope, a few studies found no association between cortisol and SES (Steptoe et al, 2005; Cohen et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…It is still uncertain which specific features of the daily cortisol profile may be most relevant to health outcomes; however, several features have been examined in relation to SES and race/ethnicity. Features of the daily cortisol curve examined in the literature include wake-up levels (Steptoe et al, 2003; Kunz-Ebrecht et al, 2004; Ranjit et al, 2005a; Wright and Steptoe, 2005; Cohen et al, 2006a; Cohen et al, 2006b; Eller et al, 2006) the CAR (Steptoe et al, 2003; Bennett et al, 2004; Kunz-Ebrecht et al, 2004; Steptoe et al, 2005; Wright and Steptoe, 2005; Cohen et al, 2006b; Eller et al, 2006; Garcia et al, 2008) and the diurnal cortisol slope (Ockenfels et al, 1995; Steptoe et al, 2005; Cohen et al, 2006a; Cohen et al, 2006b; DeSantis et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Features of the cortisol daily curve, including wake-up levels, the CAR and the diurnal cortisol slope, have been associated with socio-demographic factors, psychosocial factors, and measures of physical and mental health (Steptoe et al, 2003; Kunz-Ebrecht et al, 2004; Bennett et al, 2004; Steptoe et al, 2005; Wright and Steptoe, 2005; Cohen et al, 2006; Eller et al, 2006; DeSantis et al, 2007; Garcia et al, 2008; Champaneri et al, 2012, 2013). However, findings have not always been consistent and there is still substantial uncertainty regarding what features of the cortisol daily curve are most affected by social or psychosocial antecedents and most predictive of future health outcomes.…”
mentioning
confidence: 99%
“…Thus, it could be argued that unstable and unequal social conditions to which Brazilians are exposed to, may also explain the higher basal cortisol levels these individuals showed compared to the Canadians. Supporting this hypothesis, some authors have demonstrated high cortisol levels in low SES groups [11], [45][46]. However, the relationship between SES and basal cortisol levels is quite inconsistent in the current literature.…”
Section: Discussionmentioning
confidence: 93%